Performance investigation between DSI-SLM and DSI-PTS schemes in OFDM signals - Mohammady, Somayeh; Sulaiman, Nasri; Varahram, Pooria; Mohd Sidek, Roslina; Hamidon, Mohd Nizar

(untitled)
There is a major problem in orthogonal frequency division multiplexing (OFDM) systems that is known as high peak-to-average power ratio (PAPR), thus various PAPR reduction algorithms have been introduced. Selected mapping (SLM) and Partial transmit sequence (PTS) are two of the most attractive solutions because of their good performance without distortion. However, their high computational complexity makes them impractical solution in high-speed data transmission. In this paper, two PAPR reduction algorithms of DSI-SLM and DSIPTS are compared together. In the proposed schemes, the computational complexity is claimed to be reduced significantly by inserting dummy sequences in zero slot of OFDM signal, though they show similar performance in terms of PAPR reduction and bit error rate (BER), although deeper discussion is provided for future algorithms.